2015
DOI: 10.1155/2015/536537
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Characterization of Bordetella pertussis Clinical Isolates Associated with a California State Pertussis Outbreak

Abstract: Bordetella pertussis (Bp) is the etiologic agent of pertussis (whooping cough), a highly communicable infection. Although pertussis is vaccine preventable, in recent years there has been increased incidence, despite high vaccine coverage. Possible reasons for the rise in cases include the following: Bp strain adaptation, waning vaccine immunity, increased surveillance, and improved clinical diagnostics. A pertussis outbreak impacted California (USA) in 2010; children and preadolescents were the most affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, there are several limitations with 2D gels including that it cannot analyze the whole proteome and that less abundant yet equally important proteins may be missed . Williamson et al employed shotgun proteomics to also compare the differences in expression of vaccine antigens in the whole cell and supernatant. This study found differences in the expression of ACV antigens between current clinical strains from California and Tohama I.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, there are several limitations with 2D gels including that it cannot analyze the whole proteome and that less abundant yet equally important proteins may be missed . Williamson et al employed shotgun proteomics to also compare the differences in expression of vaccine antigens in the whole cell and supernatant. This study found differences in the expression of ACV antigens between current clinical strains from California and Tohama I.…”
Section: Introductionmentioning
confidence: 73%
“…In the whole cell, 202 proteins (24%) detected have been previously found to be immunogenic while in the secretome there were 91 immunogenic proteins (43%) . The difference was significant using a Fisher's exact test ( p < 0.0001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, increased abundance of the BP3831 protein in the secretome of the Australian epidemic strain was documented and suggested to be linked with increased fitness of this strain (Luu et al 2018). Furthermore, BP3831 protein was identified within the surface proteome of B. pertussis and was also found to be immunogenic (Tefon et al 2011;Williamson et al 2015). B. pertussis as a strictly human pathogen faces upon infection several stresses resulting from nutrient scarcity as well as from the immune response of the host.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic pattern of this unique clone was similar to that of the most common profile of BpSR11 clone in European countries [22]. Since B. pertussis evolves by time, recent studies have suggested that the use of circulating strains in improved wP or aP vaccines might be an appropriate mean to decrease and eventually eradicate B. pertussis from the globe [23,24,13]. It is also envisaged that data gathered from monitoring and characterization of B. pertussis circulating isolates would lead to a new generation of wP vaccines with better efficacy than today's vaccines.…”
Section: Introductionmentioning
confidence: 53%